Oh, what a happy little question! An equivalent expression for 6x plus 3 would be 3(2x + 1). You see, we're just factoring out a common factor of 3 from both terms to simplify it a bit. Just remember, there are many ways to express the same idea in math, just like there are many ways to paint a beautiful sky.
(6x^5-4x^2)+(2x^3-3) = 6x^5-4x^2+2x^3-3 The grestest exponent is 5, which is the degree of the above expression.
It's a binomial expression in 'x'.If you want to know its numerical value, you have to know how much 'x' is.Or at least you have to know how much the whole (6x+3) is.
If you mean 6x+3-27+15 then it is an expression that can be simplified to: 6x-9
5(3 + 16)
x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3
4x plus 3 plus 2x is equivalent to expression 6x plus 3.
Simple,its just like this: 6x+1+7-3 =6x+8-3 =6x+5
It is: 11-6x as a simplified expression
4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2
-147 - 42 + 3 = -186
It is an algebraic expression in the form of: 6x+3
The given expression can be simplified to: -6x-7
The expression is 33.
(6x^5-4x^2)+(2x^3-3) = 6x^5-4x^2+2x^3-3 The grestest exponent is 5, which is the degree of the above expression.
3
6x + 60 + 4/3 = 6x + 184/3
It's a binomial expression in 'x'.If you want to know its numerical value, you have to know how much 'x' is.Or at least you have to know how much the whole (6x+3) is.